Evaluation of the healing potential of asphalt mixtures based on a modified semi-circular bending test. (30th January 2019) - Jiang, Jiwang; Ni, Fujian; Wu, Fan; Sadek, Husam; Lv, Quan
Highlights: An optimal rest period of 0.8s were determined. Newly healing indexes were proposed. Both binder properties and gradation affect the healing potential of asphalt mix. The reliability of the newly proposed healing-based cyclic SCB test was validated. Abstract: Since the semi-circular bending (SCB) test has been widely used to evaluate the fatigue properties of asphalt mixtures, it has been modified in this paper by adding a certain length of rest period in each cyclic loading sequence to evaluate the healing potential of different asphalt mixtures. The digital image correlation (DIC) method was utilized to characterize the tensile strain at the bottom of specimens during the healing-based cyclic SCB test. The influence of notch depth of the specimen (0 mm, 15 mm and 25 mm) and the length of the rest period (0 s, 0.4 s, 0.8 s and 1.2 s) on the fatigue and healing behaviour were carefully evaluated. The fatigue life (Nf ), total dissipated energy (Gsum ), secant modulus (Ms ), average deformation growth rate (Dr ) and average tensile strain (εr ) during the cyclic load with or without rest period were analysed. Test results show that the inserted notch reduces the fatigue life and deformation of specimens, while can hardly change the load-sensitivity and secant modulus of the specimen. Most performance recovery happens within the rest period of 0.8 s. So it is better to conduct the healing-based cyclic test with non-notched SCB specimen and 0.8 s rest period. Additionally, it is found that asphalt mixtures with modified binder present both better fatigue and healing properties than asphalt mixtures with neat asphalt, while the stone matrix asphalt mixture presents similar fatigue property but much better healing potential than one dense graded mixture with the same binder.